2008 IEEE 19th International Symposium on Personal, Indoor and Mobile Radio Communications 2008
DOI: 10.1109/pimrc.2008.4699800
|View full text |Cite
|
Sign up to set email alerts
|

Polarization characteristics of multiple-input multiple-output channels

Abstract: Abstract-In this paper, we investigate the polarization characteristics of the multiple-input multiple-output (MIMO) channels. The cross polarization discrimination (XPD) is found to change over time, while its variation in frequency domain is relatively small. The probability density function (PDF) of the XPD follows a Gaussian distribution. Analysis and measurement results show that the polarization preserves better in the line of sight (LOS) scenario. In the case of non line of sight (NLOS) scenario, the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It is verified that the MIMO capacity is determined by the SNR and the eigenvalue ratio as shown in Equation (7). However, it is obvious that DP displays a few fluctuations of the eigenvalue ratio relative to the NRSSI changes as shown in Fig.6.…”
Section: Measurement Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…It is verified that the MIMO capacity is determined by the SNR and the eigenvalue ratio as shown in Equation (7). However, it is obvious that DP displays a few fluctuations of the eigenvalue ratio relative to the NRSSI changes as shown in Fig.6.…”
Section: Measurement Resultsmentioning
confidence: 79%
“…However, it has been reported that the XPDs of the V and H polarization in NLOS are highly dependent on the specific propagation environment between the transmitter and receiver because the polarization dependency of the signals is weakened due to multiple reflections, diffractions and scattering [7], while the XPD increases in a LOS environment. Then, we introduce the normalized RSSI which represents the difference from the RSSI when free space propagation is assumed.…”
Section: Measurement Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One is a cylinder with 8 cross-polarized patch antennas on the surface arranged in a row. The other is a cylindrical antenna made of two 12-patch elements arranged in two rows, on top a cube antenna is mounted as shown in [13].…”
Section: Measurement Setupmentioning
confidence: 99%